Peso muerto en la resistencia anaeróbica en adolescentes - Guzmán Rodríguez, César Rubén (2025)
The objective of the current research project, “The Deadlift in Anaerobic Endurance in Adolescents," seeks to determine how the use of the burpee test affects the measurement of anaerobic endurance in second-year high school adolescents at Juan de Velasco School. As a means of gathering data, a pretest and posttest were employed to assess and contrast the outcomes. A training plan using the deadlift exercise was implemented for 12 weeks to improve anaerobic endurance. These training plans follow a strict exercise order. The exercises were performed in three parts: the initial phase, the training execution phase, and the final phase, which includes a cool-down to promote the desired results in the adolescents at the school. The study is characterized as quasi-experimental because it was focused on collecting data before and after. By using a training plan, it was able to determine positive results. These results enabled to compare the anaerobic endurance of adolescents before and after the training plan, obtaining a p-value of 0.03, which gives this research statistical significance. This improved the anaerobic endurance of the second-year adolescents at Juan de Velasco School, demonstrating the effectiveness of the intervention